Global Voices from the Women's Library at the World's Columbian Exposition Feminisms, Transnationalism and the Archive - Dalbello, Marija; Wadsworth, Sarah (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
Long recognized as a cultural watershed and touchstone of modernity, the 1893 Chicago World's Fair (World's Columbian Exposition) was the site of the first large-scale international library of writing by women. The result of years of planning and cooperation by women's organizations in twenty-four countries from North America, South America, Europe, Asia, and the Middle East, the library of the Woman's Building contained more than 8,000 volumes, with more than 3,000 from countries other than the United States. This book collects the work of feminist scholars specializing in different national traditions and transnational comparative analysis and focuses on the contributions of the international (non-US) women's committees to extend our understanding of women's contribution to global print culture and the extension of women's rights up to 1893. Marija Dalbello is Professor at Rutgers University, USA. Sarah Wadsworth is Professor at Marquette University, USA.
1. Global Voices from the Women's Library at the World's Columbian Exposition: Feminisms, Transnationalism, and the Archive -- Part I Reading (Across) the National Collections -- 2. A Comparative and Structural Analysis of European Works in the Woman's Building Library -- 3. What Did Late Nineteenth-Century Italian Women Write? -- 4. Networks of Texts and Writers: The Swedish Contribution to the Woman's Library at the World's Columbian Exposition -- 5. "Spanish Lessons" -- Part II Gender and Modernism -- 6. Central European Collections: The Periphery Challenging the Center -- 7. How to Be a German Woman: Mixed Messages at the Columbian Exposition -- 8. The New Woman in the White City: Writing from Great Britain in the Woman's Building Library -- 9. The Norwegian Ideals of Modern Womanhood and Identity Construction through the Women's Library -- Part III Close Readings: Authoring Female Agency -- 10. Fatma Aliye's Invisible Authorship: A Turkish Muslim Woman Writer's Challenge to Orientalism and Patriarchy -- 11. The "Native New Woman": Material Culture and the Indian Novel in the Women's Library at the World's Columbian Exposition -- 12. From Private Lives to Public Spaces: Nineteenth-Century Peruvian Eclecticism at the Chicago World's Fair -- 13. French Authors at the Women's Library at the World's Columbian Exposition: A Stage of Feminism, Still Traditional Works -- 14. The Library as Exhibition -- .
Keywords: Women -- History; World history; Civilization -- History; Books -- History; Women's History / History of Gender; World History, Global and Transnational History; Cultural History; History of the Book